Comprehensive analysis of microRNA expression profile in malignant glioma tissues. Issue 7 (25th March 2015) - Piwecka, Monika; Rolle, Katarzyna; Belter, Agnieszka; Barciszewska, Anna Maria; Żywicki, Marek; Michalak, Marcin; Nowak, Stanisław; Naskręt-Barciszewska, Mirosława Z.; Barciszewski, Jan
Abstract : Malignant gliomas represent the most devastating group of brain tumors in adults, among which glioblastoma multiforme (GBM) exhibits the highest malignancy rate. Despite combined modality treatment, GBM recurs and is invariably fatal. A further insight into the molecular background of gliomagenesis is required to improve patient outcomes. The primary aim of this study was to gain broad information on the miRNA expression pattern in malignant gliomas, mainly GBM. We investigated the global miRNA profile of malignant glioma tissues with miRNA microarrays, deep sequencing and meta‐analysis. We selected miRNAs that were most frequently deregulated in glioblastoma tissues, as well as in peritumoral areas, in comparison with normal human brain. We identified candidate miRNAs associated with the progression from glioma grade III to glioma grade IV. The meta‐analysis of miRNA profiling studies in GBM tissues summarizes the past and recent advances in the investigation of the miRNA signature in GBM versus noncancerous human brain and provides a comprehensive overview. We propose a list of 35 miRNAs whose expression is most frequently deregulated in GBM patients and of 30 miRNA candidates recognized as novel GBM biomarkers. Highlights: Using microarrays and deep sequencing to characterize miRNAs in glioma tissues. Meta‐analysis provided a panel of 35 glioblastoma‐related miRNAs. 30 novel miRNA biomarkers of glioblastoma were identified. 25 candidate miRNAs associated with malignant glioma progression are reported. The resulting miRNA list provide potential therapeutic targets for glioblastoma.